ACUTE RENAL FAILURE IN INTRAOPERATIVE LESION OF BOTH URETERS FOLLOWING HYSTEROADNEXECTOMY- CASE REPORT - Simonovska, Daniela; Stojkovski, Ljupco; Popov, Zhivko; Petrovski, Daniel; Trajkovski, Zoran; Canevska-Tanevska, Aleksandra (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Intraoperative injury of the ureters and the bladder during hysterectomy is not uncommon. Lesion of both ureters is much rarer condition and it occurs in 5% to 10% of injury cases. Acute renal failure develops in case of ligation of both ureters. Diagnosis of this condition, intraoperatively or in the first seven postoperative days at the latest, allows complete recovery of the renal function. A 44-year-old women was admitted at the Department of Nephrology at Acibadem Sistina Hospital in Skopje due to anuria, lower abdominal pain and nausea. On admission the patient had increased creatinine levels and sonography finding of grade 3 hydronephrosis bilaterally. Two days earlier the patient underwent hysterectomy and adnexectomy by Pfannensteil due to myoma. MRI of lesser pelvis without contrast and retrograde urethrocystography were performed for diagnostic purposes. A bilateral prevesical lesion of the ureters was found. Upon the admission, the patient underwent two consecutive haemodialysis sessions. On the fourth day after the first surgery (hysterectomy) the patient was transferred to the Department of Urology where a surgery: bilateral ureterocystoneostomy (sec. Litch-Gregoire) was performed the same day. Following surgery the patient went in to polyuria with rapid normalization of the renal function. On the sixth postoperative day, the patient was discharged from the hospital in good general condition. In case of anuria following hysterectomy, a mechanical lesion of the ureters should be suspected. Early diagnosis allows for complete rehabilitation without consequences to the renal function. Keywords : acute renal failure, intraoperative ureteral lesion, hysterectomy, haemodialysis. https://doi.org/10.55302/JMS2143076s